Kajian Semiotik Kesetiaan Seorang Kekasih dalam Lagu Campursari Banyu Langit Karya Didi Kempot - Safarina, Reny Anindhita; Werdiningsih, Yuli Kurniati (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The purpose of writing this paper is to fulfill lecture assignments and describe one's loyalty in a campursari song with the title Banyu Langit, which was created by Didi Kempot. As a singer, Didi Kempot describes how someone who really misses his lover who never leaves but he still remembers and loves his lover. The method used in this research is descriptive qualitative. The research data is in the form of campursari song lyrics which express a person's loyalty and patience in waiting for his lover. The theory used is a semiotic study which explains the meaning contained in literary works, because every literary work has its own meaning. The result of this study is that there is a patient attitude of someone who waits for his lover with all the longing and loyalty for the sake of waiting for the lover he loves so much. Loyalty of someone who keeps his promise to stay in love and loyal to his lover by holding back longing to wait for the lover who left and never came home. The effort that a person makes in waiting for his loved one to return is proof of one's loyalty to his partner as a form of deep love and longing for his loved one.